2016
DOI: 10.1084/jem.20160157
|View full text |Cite
|
Sign up to set email alerts
|

Notch activation drives adipocyte dedifferentiation and tumorigenic transformation in mice

Abstract: Adipocyte-specific activation of Notch signaling suppresses lipid metabolism pathways that provide ligands to Pparγ, leading to adipocyte dedifferentiation and development of liposarcomas (LPSs) resembling human dedifferentiated LPSs with complete penetrance. Pparγ ligand supplementation prevents liposarcoma development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 68 publications
(91 reference statements)
3
82
0
Order By: Relevance
“…We found that the constitutively active form of Notch1 (N1ICD) upregulated Ascl2 in both myoblasts and muscle tissues. Consistently, overexpression of N1ICD also upregulates Ascl2 in adipose tissues (Bi et al, 2016). Our observation is consistent with the report that Rbpj binds to the promoter of Ascl2, and that the N1ICD-Rbpj complex directly activates Ascl2 in skin epidermis (Moriyama et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…We found that the constitutively active form of Notch1 (N1ICD) upregulated Ascl2 in both myoblasts and muscle tissues. Consistently, overexpression of N1ICD also upregulates Ascl2 in adipose tissues (Bi et al, 2016). Our observation is consistent with the report that Rbpj binds to the promoter of Ascl2, and that the N1ICD-Rbpj complex directly activates Ascl2 in skin epidermis (Moriyama et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…| 17971 mice (Bi et al, 2014). More interestingly, a recent study demonstrated that activation of Notch induces dedifferentiation of MA and promotes tumorigenic transformation in mice (Bi et al, 2016). Battle et al (2014) demonstrated that obesity-induced leptin-notch signaling in BCa.…”
Section: Discussionmentioning
confidence: 99%
“…During 3T3-L1 adipocyte differentiation, significant changes in the lipidome, including specific TAG species and sphingomyelins, have been observed (33). Conversely, de-differentiation of primary, mature adipocytes is associated with changes in the abundance of specific lipid species (4). When taken together, these findings suggest that identification of specific lipidomic signatures could be an alternative approach to assess adipocyte maturity.…”
Section: Knockdown Of 14-3-3z Is Associated With Distinct Changes Inmentioning
confidence: 99%